Customer Buying Interest: Advertising Attractiveness - Yassir (Journal of Management, 2024)
This study seeks to examine the impact of advertising viewpoint on the attractiveness of Makassar advertising. This study employs the quantitative PLS approach. The results show that the variable advertising views has a significant influence on advertising credibility, advertising attractiveness has a significant influence on advertising credibility, purchasing interest, advertising attractiveness has a significant influence on purchasing interest, and simultaneously advertising views and advertising attractiveness. The findings reveal that managers must leverage other advertising stars from diverse circles such as businesspeople, sportsmen, and community leaders to capture visitors' attention